The differential outcomes effect using sensory outcomes in a many-to-one matching-to-sample task - Rebeca Mateos Morfín, Laura; Flores, Carlos; Bruce Overmier, J. (Psicologia: Teoria e Pesquisa, 2019)
The present study was designed to examine the use of sensory outcomes (visual vs. auditory) using a differential outcomes procedure to facilitate learning in a many-to-one matching-to-sample task. For one group of participants (differential outcomes) each correct stimulus-choice sequence was always followed by a different outcome; whereas for the rest of participants (non-differential outcomes) each correct sequence was followed by the same outcome. Participants trained with differential outcomes showed a faster acquisition and higher overall accuracy than participants trained with non-differential outcomes. The results provide a new extension the differential outcomes effect by using sensory outcomes and many-to-one matching to-sample task; applications of the differential outcomes procedure are discussed.